Preparation and Characterization of Cu-Based Catalysts for Methanol Synthesis in MeOH-FPSO Process - Lee, Jin Hee; Lee, Seung Hwan; Moon, Dong Ju (AMER SCIENTIFIC PUBLISHERS, 2013)
A series of Cu-ZnO based catalysts have been synthesized by the wet impregnation method at different pH, and after calcinations, have been evaluated for the synthesis of methanol in the temperature range 220 to 260 degrees C at 35 bar with space velocity of 3,000 h(-1) and feed molar ratios of H-2/CO = 2. The catalysts have been characterized by XRD, SEM, elemental analysis, surface area and porosity measurements. It is found that the catalyst synthesized at pH 7 is most active with a CO conversion of 35.7% and a methanol selectivity of 98.1% and this can be used as an efficient catalyst for the MeOH-FPSO process.
Keywords: STABILITY; CO2